2006
DOI: 10.1124/dmd.106.009936
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Constitutive Mouse Hepatic Cytochromes P450 and Growth Hormone Signaling Components by 3-Methylcholanthrene

Abstract: ABSTRACT:3-Methylcholanthrene (MC) activates the aryl hydrocarbon receptor and increases expression of cytochrome P450 (P450) enzymes such as CYP1A1. MC also decreases expression of CYP2C11, the major hepatic P450 in male rats that is regulated by pulsatile growth hormone (GH) secretion via a pathway partially dependent on signal transducer and activator of transcription 5b (STAT5b). If disruption of this GH signaling pathway is important for MC's ability to suppress CYP2C11 transcription, we hypothesize that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
36
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(41 citation statements)
references
References 38 publications
4
36
0
Order By: Relevance
“…Similar to the suppression of rat CYP2C11 by aromatic hydrocarbons, we showed that MC treatment of male mice caused downregulation of hepatic Cyp2d9 at the mRNA, protein and catalytic activity levels (Lee et al 2006), and this was accompanied by decreased mRNA levels for the GH receptor (GHR) and major urinary protein 2 (MUP2), a GH-regulated and STAT5b-dependent transcript. Others have shown that treatment of mice with MC leads to an AHR-dependent decrease in hepatic levels of mRNA encoding GHR, Janus kinase 2 (JAK2) and two distinct STAT5b targets, MUP2 and cytokine-inducible Src homology 2 domain-containing protein (CIS) (Nukaya et al 2004).…”
Section: Introductionmentioning
confidence: 69%
See 4 more Smart Citations
“…Similar to the suppression of rat CYP2C11 by aromatic hydrocarbons, we showed that MC treatment of male mice caused downregulation of hepatic Cyp2d9 at the mRNA, protein and catalytic activity levels (Lee et al 2006), and this was accompanied by decreased mRNA levels for the GH receptor (GHR) and major urinary protein 2 (MUP2), a GH-regulated and STAT5b-dependent transcript. Others have shown that treatment of mice with MC leads to an AHR-dependent decrease in hepatic levels of mRNA encoding GHR, Janus kinase 2 (JAK2) and two distinct STAT5b targets, MUP2 and cytokine-inducible Src homology 2 domain-containing protein (CIS) (Nukaya et al 2004).…”
Section: Introductionmentioning
confidence: 69%
“…We showed previously that MC treatment caused a dramatic decrease in mouse hepatic CYP3A11 content, particularly at the protein level (Lee et al 2006). TCDD caused a 76% decrease in hepatic CYP3A11 mRNA levels in wild-type mice and this suppression response was not observed in Ahr −/− mice (Fig.…”
Section: Constitutive Hepatic Cytochromes P450 and Pormentioning
confidence: 99%
See 3 more Smart Citations